Validation of Differentially Expressed Immune Biomarkers in Latent and Active Tuberculosis by Real-Time PCR - Perumal, Prem; Abdullatif, Mohamed Bilal; Garlant, Harriet N.; Honeyborne, Isobella; Lipman, Marc; McHugh, Timothy D.; Southern, Jo; Breen, Ronan; Santis, George; Ellappan, Kalaiarasan; Kumar, Saka Vinod; Belgode, Harish; et al. (Frontiers in Immunology, 2021)
Tuberculosis (TB) remains a major global threat and diagnosis of active TB ((ATB) both extra-pulmonary (EPTB) and pulmonary (PTB)) and latent TB (LTB) remains challenging, particularly in high-burden countries which still rely heavily on conventional methods. Although molecular diagnostic methods are available e.g. Cepheid GeneXpert, they are not universally available in all high TB burden countries. There is intense focus on immune biomarkers for use in TB diagnosis, which could provide alternative low-cost, rapid diagnostic solutions. In our previous gene expression studies, we identified peripheral blood leukocyte (PBL) mRNA biomarkers in a non-human primate TB aerosol-challenge model. Here, we describe a study to further validate select mRNA biomarkers from this prior study in new cohorts of patients and controls, as a prerequisite for further development. PBL mRNA was purified from ATB patients recruited in the UK and India, LTB and two groups of controls from the UK (i) a low TB incidence region (CNTRLA) and (ii) individuals variably-domiciled in the UK and Asia ( (CNTRLB), the latter TB high incidence regions). Seventy-two mRNA biomarker gene targets were analysed by qPCR using the Roche Lightcycler 480 qPCR platform and data analysed using GeneSpringTM 14.9 bioinformatics software. Differential expression of fifty-three biomarkers was confirmed between MTB infected, LTB groups and controls, seventeen of which were significant using analysis of variance (ANOVA): CALCOCO2, CD52, GBP1, GBP2, GBP5, HLA-B, IFIT3, IFITM3, IRF1, LOC400759 (GBP1P1), NCF1C, PF4V1, SAMD9L, S100A11, TAF10, TAPBP and TRIM25. These were analysed using receiver operating characteristic (ROC) curve analysis. Single biomarkers and biomarker combinations were further assessed using simple arithmetic algorithms. Minimal combination biomarker panels were delineated for primary diagnosis of ATB (both PTB and EPTB), LTB and identifying LTB individuals at high risk of progression which showed good performance characteristics. These were assessed for suitability for progression against the standards for new Tuberculosis diagnostic tests delineated in the published World Health Organisation (WHO) technology product profiles (TPPs).